The Effect of Quality Kindergarten Services - Badriyah, Nurul (Early Childhood Research Journal (ECRJ), 2020)
Early Childhood Education Institutions have been spread in various regions because they see the importance of education, one of which is in the district of Colomadu. At this time, Early Childhood Education institutions are trying to improve their quality in order to attract parents' interest in order to increase parental satisfaction. The purpose of this study was to determine the quality of kindergarten institutions and the level of satisfaction of parents in the district of Colomadu. Subjects in this study were 575 parents of kindergarten institutions in Subdistrict of Colomadu. Sampling using a random propotional sample methodso as many as 73 parents obtained parents. Data collection techniques used questionnaire method, documentation. Data collected were analyzed using descriptive analysis and simple regression analysis. Based on the calculation of simple linear regression coefficient test data obtained (R2 )) equal to 0.174 which implies that the influence of the independent variable (TK service quality) on the dependent variable (the level of parental satisfaction) is 17.4% while the remaining 83.6% is influenced by other factors. And obtained t count 3.864 and obtained value of t table = 1.993 with a significance level of 0.05, then t arithmetic = 3.864 t table = 1.993 so that H0 is rejected and Ha is accepted. Means it can be concluded that there is a significant influence (significance) between the quality of kindergarten services on the level of satisfaction of parents in the Colomadu District 2018/2019.